The Effect of Expert Performance Microtiming on Listeners' Experience of Groove in Swing or Funk Music - Senn, Olivier; Kilchenmann, Lorenz; von Georgi, Richard; Bullerjahn, Claudia (Frontiers in Psychology, 2016)
This study tested the influence of expert performance microtiming on listeners' groove experience. Two professional rhythm section (bass/drums) performances in swing and funk style were recorded, and the performances' original microtemporal deviations from a regular metronomic grid were scaled to several magnitude levels. Music expert (n=79) and non-expert (n=81) listeners rated the groove qualities of stimuli using a newly developed questionnaire that measures three dimensions of the groove experience (Entrainment, Enjoyment, and the absence of Irritation). Findings show that music expert listeners were more sensitive to microtiming manipulations than non-experts. Across both expertise groups and for both styles, groove ratings were high for microtiming magnitudes equal or smaller than those originally performed and decreased for exaggerated microtiming magnitudes. In particular, both the fully quantized music and the music with the originally performed microtiming pattern were rated equally high on groove. This means that neither the claims of PD theory (that microtiming deviations are necessary for groove) nor the opposing exactitude hypothesis (that microtiming deviations are detrimental to groove) were supported by the data.